Risks associated with the technological adoption of industrial symbiosis: A study of its implementation by geographic regions - Diaz, Jaime Segura; Escandon-Barbosa, Diana; Salas-Paramo, Jairo (International Journal of Management and Sustainability, 2024)
This research investigates the factors influencing the adoption of industrial symbiosis practices, focusing on their relevance in geographical contexts within developing countries associated with the European Economic Community. The study employs geographical weighting analysis as its primary methodology, allowing for a nuanced examination of variable impacts within specific geographic regions. Data is gathered through surveys distributed to companies operating in various high-energy consumption sectors that have previously engaged in industrial symbiosis activities to varying extents. The study’s findings emphasize the crucial role that financial and performance-related risks played in influencing the decision-making process surrounding the implementation of industrial symbiosis. Furthermore, the research highlights the significance of regional dynamics in influencing waste disposal practices and the overall success of industrial symbiosis initiatives. Additionally, the study underscores the impact of social media and networks in disseminating vital information that is instrumental in advancing innovative industrial symbiosis processes. These findings hold practical implications for stakeholders, including policymakers, businesses, and organizations aiming to foster sustainable economic practices. Understanding the influence of risk factors and regional intricacies enables tailoring strategies that can promote industrial symbiosis adoption. Moreover, recognizing the pivotal role of social media and networks in knowledge dissemination can accelerate the adoption of novel practices, facilitating the transition towards greener economies in developed and developing regions associated with the European Economic Community.